Maternal obesity alters endoplasmic reticulum homeostasis in offspring pancreas - Soeda, Jumpei; Mouralidarane, Angelina; Cordero, Paul; Li, Jiawei; Nguyen, Vi; Carter, Rebeca; Kapur, Sabrina R; Pombo, Joaquim; Poston, Lucilla; Taylor, Paul D; Vinciguerra, Manlio; Oben, Jude A (Journal of physiology and biochemistry, 2016)
The prevalence of non-alcoholic fatty pancreas disease (NAFPD) is increasing in parallel with obesity rates. Stress-related alterations in endoplasmic reticulum (ER), such as the unfolded protein response (UPR), are associated with obesity. The aim of this study was to investigate ER imbalance in the pancreas of a mice model of adult and perinatal diet-induced obesity. Twenty female C57BL/6J mice were assigned to control (Con) or obesogenic (Ob) diets prior to and during pregnancy and lactation. Their offspring were weaned onto Con or Ob diets up to 6 months post-partum. Then, after sacrifice, plasma biochemical analyses, gene expression, and protein concentrations were measured in pancreata. Offspring of Ob-fed mice had significantly increased body weight (p < 0.001) and plasma leptin (p < 0.001) and decreased insulin (p < 0.01) levels. Maternal obesogenic diet decreased the total and phosphorylated Eif2α and increased spliced X-box binding protein 1 (XBP1). Pancreatic gene expression of downstream regulators of UPR (EDEM, homocysteine-responsive endoplasmic reticulum-resident (HERP), activating transcription factor 4 (ATF4), and C/EBP homologous protein (CHOP)) and autophagy-related proteins (LC3BI/LC3BII) were differently disrupted by obesogenic feeding in both mothers and offspring (from p < 0.1 to p < 0.001). Maternal obesity and Ob feeding in their offspring alter UPR in NAFPD, with involvement of proapoptotic and autophagy-related markers. Upstream and downstream regulators of PERK, IRE1α, and ATF6 pathways were affected differently following the obesogenic insults.
Keywords: signální dráha UPR; autofagie; leptin; Lactation; Pancreas; Pancreatitis; Maternal Nutritional Physiological Phenomena; Pregnancy Complications; komplikace těhotenství; Obesity; těhotenství; vývojová regulace genové exprese; inzulin; Dietary Sucrose; myši inbrední C57BL; Autophagy; Insulin; Leptin; Diet, High-Fat; konzumní sacharóza; dieta s vysokým obsahem tuků; stres endoplazmatického retikula; Unfolded Protein Response; Gene Expression Regulation, Developmental; Weaning; ženské pohlaví; zvířata; Endoplasmic Reticulum Stress; Pregnancy; biologické markery; laktace; obezita; odstavení; Biomarkers; Female; pankreatitida; fyziologie výživy v mateřství; pankreas; Mice, Inbred C57BL; Animals